Impact of Integrated Agronomic Practices on Raya and Gram Production Under Rainfed Condi Tions - Malik, A S; Singh, Jagdev; Faroda, A S (Annals of Arid Zone, 2016)
Improved varieties, improved management (sowing with ridger seeder and proper hoeing and weeding) and recommended dose of N and P fertilizers (40 Kg N + 20 Kg P2O5 ha for raya and 20 Kg N + 40 kg P2O5 ha for gram) gave maximum average yield of raya (18.3 q/ha) and gram (20.1 q/ha). Improved varieties of raya (Prakash) and gram (H-208) alone gave 50 and 92 per cent higher yield. respectively, over local varieties. The yields of raya and gram with improved management practices were 40 and 51 per cent higher. respectively, than conventional management. In both the management practices, the recommended dose of fertilizers gave significantly higher yield over one-third but was at par to two-third of the recommended dose.